MATHEMATICAL MODELING OF THE PROCESS OF SYNTHETIC SILUMINS PRODUCTION USING THE METHOD OF REGRESSION ANALYSIS - I. V. Rafalskij; A. V. Arabej (Литьë и металлургия)
The basic mechanisms of the process of silicon restoration from alumina-matrix composite ligatures on the basis of quartz sand are established. The mathematical models, describing influence of temperature, an alloy preparation time and quantities of silica in alumina-matrix composite ligatures on silicon output in synthetic alloy, are presented.